2018
DOI: 10.1074/jbc.m117.801944
|View full text |Cite
|
Sign up to set email alerts
|

Optineurin promotes autophagosome formation by recruiting the autophagy-related Atg12-5-16L1 complex to phagophores containing the Wipi2 protein

Abstract: Autophagy is a quality-control mechanism that helps to maintain cellular homeostasis by removing damaged proteins and organelles through lysosomal degradation. During autophagy, signaling events lead to the formation of a cup-shaped structure called the phagophore that matures into the autophagosome. Recruitment of the autophagy-associated Atg12-5-16L1 complex to Wipi2-positive phagophores is crucial for producing microtubule-associated protein 1 light chain 3-II (LC3-II), which is required for autophagosome f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 60 publications
5
67
0
Order By: Relevance
“…Previous studies showed that p62 plays an important role in the degradation of poly-ubiquitinated proteins under the condition of UPS impairment (Demishtein et al, 2017;Kageyama et al, 2014;Milan et al, 2015;Pankiv et al, 2007). In this study, we demonstrated that p-p62 S403 (Bansal et al, 2018;Chang & Monteiro, 2015;Sundaramoorthy et al, 2017). Taken together, all the evidence suggests that UPS dysfunction may be one of core pathogenic mechanisms of ALS.…”
Section: Discussionsupporting
confidence: 55%
“…Previous studies showed that p62 plays an important role in the degradation of poly-ubiquitinated proteins under the condition of UPS impairment (Demishtein et al, 2017;Kageyama et al, 2014;Milan et al, 2015;Pankiv et al, 2007). In this study, we demonstrated that p-p62 S403 (Bansal et al, 2018;Chang & Monteiro, 2015;Sundaramoorthy et al, 2017). Taken together, all the evidence suggests that UPS dysfunction may be one of core pathogenic mechanisms of ALS.…”
Section: Discussionsupporting
confidence: 55%
“…Similar channeling of Rab8a to ATG8CL-autophagosomes occurs during carbon starvation (Figure 4), suggesting that PexRD54 could mimic a host autophagy adaptor that regulates autophagy under nutrient deprivation. Interestingly, the mammalian autophagy cargo receptor Optineurin also interacts with both LC3 (mammalian ATG8 isoform) and Rab8a in mice (Bansal et al, 2018; Vaibhava et al, 2012). Although the functional implications of these interactions are unclear, a proposed model suggests that Optineurin mediates pre-autophagosomal membrane elongation through anchoring Rab8a to autophagosome assembly sites.…”
Section: Discussionmentioning
confidence: 99%
“…Optineurin promotes aggregation of mutant huntingtin and mutant ataxin-3: Optineurin mediates autophagy dependent clearance of protein aggregates formed by mHtt and some other mutant proteins associated with neurodegenerative diseases in neuronal and non-neuronal cells (29,30). Recently we have generated Optn -/mouse embryonic fibroblasts (MEFs) which show reduced non-selective (basal and starvation induced) autophagy as seen by reduced formation of LC3-II, and lower number of autophagosomes and autolysosomes in comparison with wild type cells (36,44). We examined the formation of mHtt aggregates in Optn -/and wild type MEFs by expressing GFP tagged mHtt and observing under a fluorescence microscope.…”
Section: Resultsmentioning
confidence: 99%